The “Islamic State” and The New Dynamics of Terrorism in The Sahel - González, Yoslán Silverio (Department of Political Science - Universitas Sains Al-Qur’an, 2025)
The Sahel-Saharan region of West Africa has been affected by the expansion of terrorist activism. Since 2015, groups operating in the Sahel have continued their tendency toward fragmentation, driven at this stage by the emergence of the organization known as the Islamic State, whose official name is the Islamic State of Iraq and Syria (ISIS). The objective of this article is to characterize the behavior of terrorist organizations in the Sahel following the emergence of the Islamic State and how relations between previously existing groups in this area changed between 2015 and 2020. During this period, the behavior of terrorism in the vast Sahel-Saharan region has been characterized by an increase in the number of actors involved, the creation of new alliances, the fragmentation of other groups, and even the emergence of many others without a specific affiliation. Therefore, the dynamics are much more complex than those that can be determined solely by well-identified and structured groups. From this, it follows that the systems of loyalties and alliances established between them are confusing and malleable. That said, no generalizations about terrorism in the Sahel can be made, given that there is no single type of terrorism and the dynamics of each group may be different, although certain trends can be identified. The combination of all these factors made possible the occurrence of different coup d’états since 2020 in Mali, Niger and Burkina Faso, that lead to the progressive expulsion and withdrawal of French troops from those countries and also marked the collapse of Wester antiterrorism program in the Sahel, reinforcing the growing influence of Russia and China in African´s security issues.